Recent advances in transition-metal-sulfide-based bifunctional electrocatalysts for overall water splitting - Wang, Min; Zhang, Li; He, Yijia; Zhu, Hongwei (Journal of materials chemistry. A, Materials for energy and sustainability, 2021)
Hydrogen produced via water electrolysis can act as an ideal clean chemical fuel with superb gravimetric energy density and high energy conversion efficiency, solving the problems of conventional fossil fuel exhaustion and environmental contamination. Transition metal sulfides (TMS) have been extensively explored as effective, widely available alternatives to precious metals in overall water splitting. Herein, recent advances, covering preparation methods, intrinsic electrocatalytic performance, and optimization strategies, relating to TMS-based bifunctional electrocatalysts have been summarized systematically and comprehensively. Firstly, a general introduction to the reaction mechanisms and key parameters of the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is provided. Next, the physicochemical properties of TMS and typical synthesis methods are introduced to give guidance for fabricating TMS materials with well-defined structures, controllable compositions, and excellent performance. Importantly, the intrinsic activities of TMS-based electrocatalysts and several strategies for improving their bifunctional electrocatalytic performance during water electrolysis are discussed in detail. Finally, perspectives covering the challenges and opportunities related to the further development of TMS-based materials with high activity and long-term durability for overall water splitting are given. The aim herein is to provide guidelines for the design and fabrication of TMS-based bifunctional electrocatalysts with excellent performance and to accelerate their large-scale practical application in water electrolysis. This review summarizes recent advances relating to transition metal sulfide (TMS)-based bifunctional electrocatalysts, providing guidelines for the design and fabrication of TMS-based catalysts for practical application in water electrolysis.